EFFECTIVE COMMUNICATION AS THE BASIS OF THE FUTURE PROFESSIONAL ACTIVITY OF THE FOREIGN STUDENTS IN UKRAINIAN HIGHER EDUCATIONAL ESTABLISHMENTS - Годлевська, Д. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article the effective communication is considered as a condition of the future professional work of the foreign students trained in higher educational institutions of Ukraine. It is also discovered specificity of communicative process, interpersonal communications, the main communicative barriers